The effects of sous-vide cooking on the physicochemical, microbiological, and carbon footprint of buffalo meat at various temperatures and times - Phoemchalard, C.; Tathong, T.; Pornanek, P. (International Journal of Agricultural Technology, 2021)
The effects of temperature (55, 59, or 70℃) and time (24 or 48 h) on pH, surface color, browning index (BI), cooking loss (CL), color changes (∆), muscle shrinkage, shear force (SF), toughness, textural profile analysis (TPA), microbial content, and carbon footprint in sous-vide-cooked buffalo meat were examined. These quality parameters were compared with traditional cooking (TC; 80℃ for 30 min). The results showed that meat cooked by TC had higher SF, toughness, hardness, springiness, cohesiveness, gumminess, and chewiness than the other sous-vide treatments. A temperature and time combination showed a major increase in pH, a*, b*, ∆E, BI, and cohesiveness but a reduction of ∆a*, toughness, and microbial content. The CL, transversal shrinkage (TS), SF, hardness, gumminess, and carbon footprint increased with increased temperature. Almost all instrumental texture values, particularly hardness, were decreased with prolonged time. Among sous-vide treatments, the lower TS, shear tests, and almost all texture profiles were found in samples cooked at 55°C for 48 h. Compared to raw meat, there was no risk of inadequate pasteurization in cooked treatments. Thus, the results concluded that sous-vide cooking had a key advantage in retaining moisture, supplying tender meat (55°C-48 h and 59°C-24 h ), and minimizing carbon footprint (55- and 59°C-24h)